Analisis Kesiapan Rumah Sakit Umum Daerah Kramat Jati Menjadi Health Promoting Hospital Tahun 2017 - Winarto, Winarto (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2017)
The readiness of Regional General Hospital (RSUD) of Kramat Jati to become Health Promoting Hospital (HPH) is very important based on Health Promotion Standard of Ministry of Health Republic of Indonesia Year 2011. Therefore, the purpose of this research is to know the preparedness of RSUD Kramat Jati become Health Promoting Hospital, done by qualitative approach. The results showed that from six (6) standard of hospital health promotion, one (1) standard of hospital health promotion has been fulfilled by RSUD Kramat Jati, while five (5) standard of health promotion of hospital have not been fulfilled. Preparation of technical policies for the implementation of HPH by the Dinas Kesehatan, dissemination of HPH, the optimization of special unit roles, the addition of human resources, the implementation of special training education, empowerment activities and community organizing as well as further research in the assessment of standard components of hospital health promotion are proposed suggestions in this research.